(untitled) (CIPEEX, 2025)
Introduction: Obesity is currently one of the most serious public health problems. Its prevalence has been sharply increasing in recent decades, even in developing countries, which has turned it into a global epidemic. Severe obesity is a complex condition that manifests through significant alterations in the systemic levels of these inflammatory markers and biochemical components, often leading to the indication of bariatric surgery. Objective: to verify the systemic levels of biochemical components and inflammatory markers in different studies with the population with severe obesity. Methodology: Five original articles were extracted from the PubMed, Google Scholar, and Scielo databases, published between 2018 and 2024. The descriptors in Health Sciences (DeCS) used for the search were: "severe obesity," "bariatric surgery," and "biochemical markers," with the boolean operator "AND." The inclusion criteria were publications in any language, original studies, and open access. Results: In obese individuals, there is an observed increase in glucose levels, blood lipids, and inflammatory markers such as CRP and IL-6, as well as an increase in oxidative stress, which can contribute to metabolic and cardiovascular comorbidities, necessitating therapeutic interventions to modulate these markers. Conclusion: The analyzed studies demonstrated that obesity significantly impacts various biochemical markers, exacerbating both glycemic and lipid conditions and promoting a chronic inflammatory state.